A Closed-Form Solution for Estimating the Accuracy of Circular Feature' Pose for Object 2D-3D Pose Estimation System. (17th March 2021) - Li, Cui; Chen, Derong; Gong, Jiulu; Wu, Yangyu
Abstract : Many objects in the real world have circular feature. In general, circular feature's pose is represented by 5-DoF (degree of freedom) vector ξ = X, Y, Z, α, β T . It is a difficult task to measure the accuracy of circular feature's pose in each direction and the correlation between each direction. This paper proposes a closed-form solution for estimating the accuracy of pose transformation of circular feature. The covariance matrix of ξ is used to measure the accuracy of the pose. The relationship between the pose of the circular feature of 3D object and the 2D points is analyzed to yield an implicit function, and then Gauss–Newton theorem is employed to compute the partial derivatives of the function with respect to such point, and after that the covariance matrix is computed from both the 2D points and the extraction error. In addition, the method utilizes the covariance matrix of 5-DoF circular feature's pose variables to optimize the pose estimator. Based on pose covariance, minimize the mean square error (Min-MSE) metric is introduced to guide good 2D imaging point selection, and the total amount of noise introduced into the pose estimator can be reduced. This work provides an accuracy method for object 2D-3D pose estimation using circular feature. At last, the effectiveness of the method for estimating the accuracy is validated based on both random data sets and synthetic images. Various synthetic image sequences are illustrated to show the performance and advantages of the proposed pose optimization method for estimating circular feature's pose.